2019
DOI: 10.1186/s12890-019-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Using photo-elicitation to explore perceptions of physical activity among young people with cystic fibrosis

Abstract: BackgroundPhysical activity is recommended in the management of cystic fibrosis (CF). The aim of this study was to explore motives, barriers and enablers to physical activity among this population. Methods: Twelve participants (12–18 years) were recruited via convenience sampling. Photo-elicitation alongside semi-structured interviews were used to explore participants’ views and experiences of physical activity.ResultsOur findings revealed motives for physical activity including health, enjoyment and autonomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
4
8
0
4
Order By: Relevance
“…This study identified near unanimous agreement regarding the importance of PA for CF evidenced from both the qualitative and quantitative data collected from a wide international sample, although there remains considerable variation in PA practices and promotion for pwCF. In accordance with previous literature exploring the reasons for which PA is considered to be important for CF [11,15], many pwCF attributed their health, and even their life, to their PA. Health and enjoyment were two of the biggest motivators for PA among pwCF, a finding that is consistent with motives for PA among both other clinical and healthy populations [16,17]. Those motivated by the physical and psychological health benefits of PA identified how PA helped make them feel in control, and restored a sense of normality; factors that have been linked to improvements in well-being [18], quality of life [19] and improved self-management practices [20].…”
Section: Discussionsupporting
confidence: 85%
“…This study identified near unanimous agreement regarding the importance of PA for CF evidenced from both the qualitative and quantitative data collected from a wide international sample, although there remains considerable variation in PA practices and promotion for pwCF. In accordance with previous literature exploring the reasons for which PA is considered to be important for CF [11,15], many pwCF attributed their health, and even their life, to their PA. Health and enjoyment were two of the biggest motivators for PA among pwCF, a finding that is consistent with motives for PA among both other clinical and healthy populations [16,17]. Those motivated by the physical and psychological health benefits of PA identified how PA helped make them feel in control, and restored a sense of normality; factors that have been linked to improvements in well-being [18], quality of life [19] and improved self-management practices [20].…”
Section: Discussionsupporting
confidence: 85%
“…This study identified the preferences of adults with CF regarding where breathlessness and fatigue were barriers to exercise. [29][30][31][32][33][34][35] Feeling embarrassed during exercise and being unable to keep pace with peers have previously been reported as barriers to exercise for people with CF 31,33,34,36 and chronic obstructive pulmonary disease (COPD). 37 Some adults with CF also fear exercising in public due to infection control concerns.…”
Section: Discussionmentioning
confidence: 99%
“…This would also provide an option for exercise during the cold winter months, when exercise participation is often reduced. 31,33,34,36,38 Although preferences regarding format were variable, participants agreed that telehealth exercise programs should be user-friendly and accessible, considering the available equipment, space, and cost of the program. This is in line with previous research in adults, children, and adolescents with CF where cost 31,34 and limited availability of physical activity facilities 29,36 were barriers to exercise participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted in 10 countries show that the use of PEIs in health sciences allows for the active involvement of participants: Australia (Murray et al, 2019), Brazil (Ribeiro et al, 2018), Canada (Backman et al, 2018), England (Armstrong-James et al, 2019; Denford et al, 2019; Marsh et al, 2020; Pini et al, 2019; Wells et al, 2013), France (Lachal et al, 2012; Lecomte et al, 2019), Kenya (O’Brien et al, 2019), Portugal (Calha et al, 2019), Spain (Oter-Quintana et al, 2017), Sweden (Alvariza et al, 2020; Hajradinovic et al, 2018; Olausson et al, 2013), and the United States (Kantrowitz-Gordon & Vandermause, 2016; Latta et al, 2014; Stutey et al, 2016). The studies were developed with: (a) family members of adult patients at end of life (Hajradinovic et al, 2018) and in the intensive care unit (Olausson et al, 2013); (b) adolescents, in the context of dialysis treatment (Wells et al, 2013), cystic fibrosis (Denford et al, 2019), bulimia nervosa (Lecomte et al, 2019), and during the return to school after cancer treatment (Pini et al, 2019); (c) underage siblings of children with autism (Latta et al, 2014); (d) children who have lost loved ones (Stutey et al, 2016); (e) parents of preterm infants (Kantrowitz-Gordon & Vandermause, 2016); (e) mothers of newborn children (O’Brien et al, 2019) and healthy children (Murray et al, 2019); (f) elderly people attending a day hospital (Calha et al, 2019); (g) homeless women (Oter-Quintana et al, 2017); (h) health professionals (Alvariza et al, 2020; Marsh et al, 2020; Ribeiro et al, 2018); (i) families of children and adolescents with burns (Armstrong-James et al, 2019) and families of obese children (Lachal et al, 2012); and (j) families of elderly patients with multiple chronic conditions (Backman et al, 2018).…”
mentioning
confidence: 99%